Pengaruh Pemberian Ekstrak Daun Sirih (Piper betle)Terhadap Tingkat Kesembuhan dan Kelulushidupan Kepiting Bakau (Scylla seratta) yang Dimutilasi - Carolina A Deru; Yuliana Salosso; Cresca Benmar Eoh (Jurnal Akuatik, 2019)
The research has been implemented in order to know the effect of giving betel leaf extract (piper betle L) to the healing rate and survival of mutilationmud crab (scylla serrata). This research was conducted from March to May 2017 at the Laboratory of Faculty of Health and Fisheries, University of Nusa Cendana, Kupang. Mutilation mud crabs were soaked using betel leaf extract for 15 minutes and this was done for 3 consecutive days. The concentration of piper betle leaf extract used for immersion of mutilationmud crabs is 25%, 50%, and 75%. It is given as antibacterial, antioxidant, anti - inflammatory, antiseptic and to help the healing process of the wounds of mutilation mud crab. The results of Anova showed that giving piper betle leaf extract gave a real effect on the healing rate of mud crabs with 75% concentration of piper betle leaf extract that is optimal. Despite a significant effect on the rate of healing, there was no significant difference in survival of mud crabs.